ANALISIS PENGARUH KUALITAS PELAYANAN DAN CITRA KOPERASI TERHADAP LOYALITAS ANGGOTA KOPERASI PADA KOPERASI KREDIT SANGOSAY BAJAWA - Hyronimus Hyronimus; Lambertus Langga (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
This study aims to analyze the influence of service quality and cooperative image on the loyalty of cooperative members at the Sangosay Bajawa credit cooperative. This research is quantitative research. This study uses a causal approach. Research to examine the relationship between the variables that exist in the hypothesis. The population in this study was 16,868 people with a sample of 100 members in 2020. The analysis used was SPSS version 25. The results showed that service quality had a significant effect on customer loyalty with a significant value of 0.189 and cooperative image had a significant effect on member loyalty with a significant value of 0.003. From the results of developing and testing the instrument, a good questionnaire set has been produced and meets the validity and reliability requirements. This shows that the variables of service quality and cooperative image have a significant effect on member loyalty. For the adjusted R square value of 0.142, this shows that the percentage of service quality variables and the image of the cooperative on member loyalty is 142% at the Sagos Credit Cooperative. While the remaining 85.8% is influenced by other factors not described in this study.